TALKING STICK LEARNING MODEL: A STRATEGY IN ENHANCING STUDENTS’ ENGLISH PROFICENCY - Candra Ning Prihatini; Dyah Sih Pratiwi; Amrizal Amrizal (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
This study aimed to know the level of students’ improvement through talking stick learning model in University of Muhammadiyah Lampung. This study composed of twenty students as the subject of this study and is anchored in Classroom Action Research (CAR). The data was collected through the pre-test and post-test and was analyzed using the average score. The result of this study revealed that Talking Learning Model can enhance the English proficiency of the students under the special needed program, University of Muhammadiyah Lampung.